2015
DOI: 10.4049/jimmunol.1501243
|View full text |Cite
|
Sign up to set email alerts
|

Oral Immunization with a Recombinant Lactococcus lactis–Expressing HIV-1 Antigen on Group A Streptococcus Pilus Induces Strong Mucosal Immunity in the Gut

Abstract: The induction of a potent humoral and cellular immune response in mucosal tissue is important for the development of an effective HIV vaccine. Most of the current HIV vaccines under development use the intramuscular route for immunization, which is relatively poor in generating potent and long-lived mucosal immune responses. Here, we explore the ability of an oral vaccination with a probiotic organism, Lactococcus lactis (L. lactis), to elicit HIV-specific immune responses in the mucosal and systemic compartme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…In the context of S. Typhi Omps, encapsulation in PLGA beads increases specific B cell responses in PPs and MLNs of orally immunized mice compared to Omps alone, suggesting the versatility of this delivery system (222). Outside chemically based delivery systems, viral and bacterial Ags expressed in safe natural carriers such as probiotic strains generate specific local and systemic protective immunity observed in case of S. Typhimurium infection in mice when fed orally (223)(224)(225)(226). Another manner to contribute to the good delivery of Ags in the intestinal mucosa would consist of orally coadministering the vaccine formulation with the protease inhibitor U-Omp19 from Brucella, which has been shown both to increase the half-life of Ags delivered along the GI tract and to activate APCs (227).…”
Section: Delivery Vehicles For Mucosal Vaccinationmentioning
confidence: 99%
“…In the context of S. Typhi Omps, encapsulation in PLGA beads increases specific B cell responses in PPs and MLNs of orally immunized mice compared to Omps alone, suggesting the versatility of this delivery system (222). Outside chemically based delivery systems, viral and bacterial Ags expressed in safe natural carriers such as probiotic strains generate specific local and systemic protective immunity observed in case of S. Typhimurium infection in mice when fed orally (223)(224)(225)(226). Another manner to contribute to the good delivery of Ags in the intestinal mucosa would consist of orally coadministering the vaccine formulation with the protease inhibitor U-Omp19 from Brucella, which has been shown both to increase the half-life of Ags delivered along the GI tract and to activate APCs (227).…”
Section: Delivery Vehicles For Mucosal Vaccinationmentioning
confidence: 99%
“…These were performed as described previously (27). Briefly, Nunc high-binding ELISA plates (Thermo Fisher Scientific; Waltham, MA, USA) were coated with 2 µg/ml of recombinant SARS-CoV-2 proteins (S1 and RBD-His proteins were produced in the lab and S1 + S2 ECD spike protein was purchased from Sino Biologicals) in Dulbecco's phosphate-buffered saline (DPBS) and incubated overnight at 4 °C.…”
Section: Measurement Of Binding Antibodies By Enzyme-linked Immunosormentioning
confidence: 99%
“…Experimental studies have shown that intranasal probiotics of Lactobacillus strains stimulate immune responses in the respiratory tract, offering protection from viral (H1N1) infection [ 107 , 108 ]. Probiotics have been used to deliver antigens or adjuvants directly to the “unfriendly” gastrointestinal tract in HIV vaccine development [ 109 ] and as a potential cryopreservative and immunomodulator of mucosal immune response in Hepatitis B vaccines [ 110 ]. Despite existing evidence on the role of probiotics to enhance vaccine-specific immunity, there is a need for rigorous longitudinal mechanistic and efficacy studies in paediatrics for different vaccines.…”
Section: Potential Solutionsmentioning
confidence: 99%